SPECIAL NEEDS EDUCATION: A CASE STUDY OF VISUAL IMPAIRMENT STUDENTS OF COMMUNITY EDUCATION STUDY PROGRAM IN IKIP SILIWANGI - Novi Widiastuti (IKIP Siliwangi Bandung, 2018)
This study focuses on adult education for special needs students of community education study program in IKIP Siliwangi. Education in this perspective covers not only the methodological problems and learning methods, but also the learning problems faced by various students. There are two categories of human characteristics: physical characteristics and mental characteristics. In physical characteristics, there are students who have different physical conditions compared to others, such as being blind or visually impaired. Nowadays, a lot of special needs students have applied inclusive learning which allows them to attend higher education. Thus, this study aims to uncover adults’ education in facilitating and encouraging special needs students.